PERBANDINGAN LUARAN ANEMIA DENGAN DAN TANPA PENYAKIT GINJAL KRONIK PADA STROKE ISKEMIK - Hamida Putri,* Kiki Muhammad Iqbal,* Rusli Dhanu* (Neurona Majalah Kedokteran Neuro Sains, 2016)
INTRODUCTION ANEMIA IS A COMMON CONSEQUENCE OF CHRONIC KIDNEY DISEASE CKD AND ALSO A POSSIBLE RISK FACTOR FOR STROKE ANEMIA CAUSES DECREASED OXYGEN CARRYING CAPACITY ALTERATIONS IN BLOOD VISCOSITY IMPAIRED CEREBRAL AUTOREGULATION AND THROUGH ITS EFFECTS ON INFLAMMATION MAY BE ASSOCIATED WITH POOR OUTCOME AFTER STROKE MECHANISM RELATIONSHIP CKD WITH WORSENING OF STROKE OUTCOME IS UNKNOWN BUT ONE STUDY SHOWED THAT INCREASED AORTIC STIFFNESS AMONG CKD PATIENTS WAS AN EXPLANATION WHY CKD IS A PREDICTOR OF CEREBROVASCULAR MORTALITY